PENGEMBANGAN INSTRUMEN TES DAN NON TES SEBAGAI ALAT EVALUASI HASIL BELAJAR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Abdan Syakuro; Sabrina Ais Zahra; Sofiatun Anisa; Farah Abidah Maryam; Siti Mutmainah; Nisrina Luthfiyah Azam; Ridho Riyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning evaluation is an essential component of the educational process, as it measures students’ achievement of learning competencies and serves as a basis for improving the quality of instruction. This article aims to examine the concept of learning evaluation, the characteristics of test and non-test instruments, the principles of instrument development, their implementation in learning, and the challenges and innovations of educational assessment in the digital era. The study employs a library research method by reviewing relevant books and scholarly articles. The findings indicate that test instruments effectively assess students’ cognitive abilities based on the principles of validity, reliability, objectivity, and practicality. In contrast, non-test instruments are designed to evaluate affective and psychomotor domains through observation, interviews, questionnaires, portfolios, and performance assessments. The development of both types of instruments should adhere to the principles of validity, objectivity, accountability, and continuity. Furthermore, innovations such as authentic assessment, digital-based evaluation, Higher Order Thinking Skills (HOTS) assessment, e-portfolios, and learning analytics contribute to more comprehensive and effective learning evaluation. The integration of test and non-test instruments is expected to enhance the quality of learning and support continuous educational improvement.